2020
DOI: 10.1021/acs.jafc.0c01855
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Quantitative Trait Loci for Flavonoids Provide New Insights into the Genetic Architecture of Strawberry (Fragaria × ananassa) Fruit Quality

Abstract: Flavonoids are products from specialized metabolism that contribute to fruit sensorial (color) and nutritional (antioxidant properties) quality. Here, using a pseudo full-sibling F1 progeny previously studied for fruit sensorial quality of cultivated strawberry (Fragaria × ananassa), we explored over two successive years the genetic architecture of flavonoid-related traits using liquid chromatography electrospray ionization tandem mass spectrometry (13 compounds including anthocyanins, flavonols, and flavan-3-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…Thus, all QTL controlling TPC and TEAC and 84.3% of mQTL controlling individual metabolites were only detected during one of the two assessed years. Similar results were recently reported by Labadie et al 20 in a different F 1 population of octoploid strawberry, in which the authors detected low stability of QTLs for flavonoids in ripe fruits. Due to their function protecting against oxidative stress from several environmental factors (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Thus, all QTL controlling TPC and TEAC and 84.3% of mQTL controlling individual metabolites were only detected during one of the two assessed years. Similar results were recently reported by Labadie et al 20 in a different F 1 population of octoploid strawberry, in which the authors detected low stability of QTLs for flavonoids in ripe fruits. Due to their function protecting against oxidative stress from several environmental factors (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…parental lines, as high as the SD observed among the F 1 progeny (Table 1). Similarly, other studies in strawberry and tomato have reported strong environmental effects over polyphenols and antioxidant capacity 19,20,[36][37][38] . Nevertheless, 15.3% of mQTLs controlling secondary metabolite content were detected in the two assessed years.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations